The Agile Development Methodology with Data Search to Design a Website-Based Mail Management Information System - Rima Tamara Aldisa; Ahmad Ilham Kushartanto (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
In the era of everything digital as it is today, it is important and requires a website to make it easier to make correspondence so that it is recorded and explained clearly. Letters are news or information in written form. A company that needs and needs to make correspondence to be sent to other departments. There are problems that need to be discussed, namely it is difficult to record letters, check letters, make letter dispositions and store incoming and outgoing letters. The Use of Agile Development Methodology with Data Search To Design a Web Site Based Mail Management Information System. By applying the Agile Development method here with a view to software development carried out in stages. Data search is here to make it easier for system users to find, find letters by simply entering a keyword you want to search for. The purpose of this study is to make it easier to record letters, check letter status, make letter dispositions, print letters, save to make it easier to make letters